1985
DOI: 10.1002/1097-0142(19851215)56:12<2902::aid-cncr2820561230>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Primary lymphoma of the liver ten cases and a review of the literature

Abstract: Ten adult white patients (21-75 years old; six women, four men) presented with large cell lymphoma of the liver. Each complained of abdominal pain and/or an abdominal mass, and five had B-symptomatology of weight loss, fever (one patient), and night sweats (three patients). At laparotomy (eight patients) or by computerized tomography, liver-spleen scan and lymphangiogram (two patients with percutaneous liver biopsy only), the liver was the sole site of involvement, although subsequent staging procedures reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(45 citation statements)
references
References 15 publications
3
40
0
2
Order By: Relevance
“…Based on liver infiltration, PHL can be subdivided into nodular or diffuse types [10]. The pattern of liver infiltration has no prognostic value [1,11]. Similarly, the disease may be of either T-or B-cell origin [10].…”
Section: Discussionmentioning
confidence: 99%
“…Based on liver infiltration, PHL can be subdivided into nodular or diffuse types [10]. The pattern of liver infiltration has no prognostic value [1,11]. Similarly, the disease may be of either T-or B-cell origin [10].…”
Section: Discussionmentioning
confidence: 99%
“…[25,26] Secondary hepatic lymphomas are defined by some authors as liver lymphomas with extra hepatic foci of lymphoma and found at the first onset or afterwards, or systemic lymphoma with secondary hepatic involvement. This description is also conflicting with the above definition of primary lymphoma.…”
Section: Classification Of Lymphomamentioning
confidence: 99%
“…[9][10][11][12] Prodromal symptoms may accompany these symptoms. 9,11 A physical examination commonly reveals hepatomegaly (in approximately 80% of cases) and, less frequently, jaundice, splenomegaly, ascites, or pleural effusions.…”
Section: Discussionmentioning
confidence: 99%